Pengaruh Rasio Keuangan Pemerintah Daerah terhadap Indeks Pembangunan Manusia - Ali Hardana; Jafar Nasution (Faculty of Economics, Universitas Internasional Batam, 2022)
Purpose - Local governments with great authority in the current era of autonomy must be able to use the allocation to the maximum for the welfare of the community. The appropriate local government fiscal policy through the Regional Revenue and Spending Budget (APBD) is expected to increase the human development index to improve the welfare of the community. This research was conducted to find out how much influence the local government financial ratios have on the human development index, the ratio used is the ratio of the degree of decentralization, the ratio of regional financial dependence, the ratio of regional financial independence, the ratio of the effectiveness of local own revenue and the ratio of the effectiveness of the local tax. Research Method - The type of data from this research is quantitative descriptive using primary and secondary data. The data analysis technique used is multiple linear regressions. Findings - The results of this research are that there is a very strong relationship between the degree of decentralization, the ratio of regional financial dependency, the ratio of regional financial independence, the ratio of the effectiveness of local own-source revenue, and the ratio of the effectiveness of local taxes and simultaneously affect the human development index. Implication – There is a very strong relationship between the degree of decentralization, the ratio of regional financial dependence, the ratio of regional financial independence, the effectiveness ratio of regional original income and the effectiveness of regional taxes and have a simultaneous (together) effect on the human development index.